The Use of Quizlet Platform as Media in Teaching Vocabulary - Hasibuan, Caren Ester; Shelvi Angella; Pangaribuan, Darman; Br Sembiring, Yenita; Rambe, Kartina Rahmadhani (ELT (English Language Teaching Prima Journal), 2025)
This study examined the utilization of the Quizlet platform for vocabulary instruction and assessed students' impressions of its application in an Indonesian EFL classroom. The research utilized a descriptive qualitative design and was conducted out at SMA Budi Utomo Medan over a duration of four weeks. The participants included 27 EFL students and one English teacher, chosen by purposive sampling. Data were gathered via classroom observations, questionnaires, and semi-structured interviews. The findings indicated that Quizlet was methodically utilized as a primary instructional resource. The teacher employed many Quizlet features, such as flashcards, matching activities, spelling drills, and Quizlet Live, to facilitate vocabulary acquisition. Students exhibited significant engagement and conveyed positive perception of the platform. Despite the identification of various hurdles, including initial difficulties and unreliable internet connectivity, these issues lessened over time. Overall, the study concluded that Quizlet served as an excellent tool for vocabulary instruction in the EFL classroom.